Time-varying effects of signs and symptoms on pregnancy loss <20 weeks: Findings from a preconception prospective cohort study - Sapra, Katherine J (Paediatr Perinat Epidemiol, 2017)
BACKGROUND: Although pregnancy loss affects one-third of pregnancies, the associated signs/symptoms have not been fully described. Given the dynamic nature of maternal physiologic adaptation to early pregnancy, we posited the relationships between signs/symptoms and subsequent loss would vary weekly. METHODS: In a preconception cohort with daily follow-up, pregnancies were ascertained by self-administered sensitive home pregnancy tests on day of expected menses. We evaluated the effects of weekly time-varying signs/symptoms (including vaginal bleeding, lower abdominal cramping, and nausea and/or vomiting) on pregnancy loss <20 weeks in Cox proportional hazards models and calculated the week-specific probability of loss by presence/absence of each sign/symptom. RESULTS: Of 341 pregnancies ascertained by home pregnancy test, 95 (28%) ended in loss. Relationships between signs/symptoms and loss varied across time since first positive pregnancy test. In the first week following pregnancy confirmation, when many losses occurred, bleeding (hazard ratio (HR) 8.7, 95% confidence interval (CI) 4.7, 16.0) and cramping (HR 1.8, 95% CI 1.2, 2.7) were associated with loss even when accompanied by nausea and/or vomiting (HR 5.2, 95% CI 2.6, 10.5). After the second week, new relationships emerged with nausea and/or vomiting inversely associated (HR range 0.6 to 0.3, all 95% CI upper bounds <1.00) and bleeding no longer associated with loss. Probabilities of loss of ranged from 78% (95% CI 59%, 96%) with bleeding present in week 1 to 8% (95% CI 5%, 12%) with nausea/vomiting present in week 5. CONCLUSIONS: Relationships between signs/symptoms and pregnancy loss vary in early pregnancy possibly reflecting maternal physiologic response.